USM GARNERS 1 GOLD, 1 SILVER AND A SPECIAL AWARD AT KIWIE 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KOREA, June 2016 Universiti Sains Malaysia (USM) has once again excelled at the global stage through its female academicians, by obtaining 1 gold, 1 silver and also a special award from the Korean Intellectual Property Office (KIPO) at the Korea International Women's Invention Exposition (KIWIE 2016).